К проблеме использования монологической речи старшими дошкольниками с аутизмом - Базыма, Н. В.
The analysis of the speech development of children with autism spectrum disorders and method for identifying communication attempts of children with autism spectrum disorders are presented in the article.
Keywords: Аутизм